Thailand as Regional Actor in South-East Asia: Experience of “Soft” Regionalism - S. Navapat (Научный диалог, 2018)
The foreign policy of Thailand and its role in regional integration processes in Southeast Asia are considered. Materials are the texts of the official websites of the government of Thailand, Ministry of Foreign Affairs of Thailand, Association of South-East Asia, its research centres, Embassy of Thailand in South-East Asia in foreign policy of Thailand relative to other countries (e.g., Singapore, Australia, Japan, Russia, etc.). It is shown that Thailand focuses foreign policy primarily on neighbouring countries, such as Laos, Myanmar, Cambodia and Malaysia. It is noted that since 2001, each Thailand government has pursued a foreign policy aimed at developing relations and cooperation with neighbouring countries. It is indicated that Thailand implements its national interests through integration processes. It is emphasized that it is trying to take a leadership position in the South-East Asia region through the creation of new agreements and regional projects that are implemented in a “soft” form, especially in its subregion. Particular attention is paid to the analysis of the role of Thailand in Southeast Asia and the peculiarities of soft regionalism in the region.